Kaum Milenial, Apakah Anda Calon Investor Kami? - Mustafa, Doni; Wibowo, Puji ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2023)
The purpose of this study is to analyze factors influencing investment decision in Indonesian government securities, namely Surat Berharga Negara (SBN) on millennials by considering several variables, namely level of income, financial literation, and investment experience both in real and financial assets. This is a quantitative research by collecting primary data through questionnaire distribution. Respondents were elected by using a purposive sampling method, whereas respondents from millennials who reside in the Jabodetabek area and fulfilled several criteria were chosen. The returned and completed surveys from 294 respondents were subsequently analyzed by adopting the ordinal regression method. This study shows us that financial literation and investment experience in financial assets have a significant effect on millennials' decision to invest in SBN. Meanwhile, level of income and investment experience in real assets show insignificant effects. This study suffers from respondent heterogeneity because the authors only focused on those who are public officers and reside in Greater Jakarta only. However, this research contributes practical implications for the Ministry of Finance to enhance its financial literation campaigns by conducting and developing various methods that are favorable for millennials.